The Effect of Flashcard Education on Premarital Sexual Behavior in Adolescent - Latifah Susilowati; Dwi Yati; Lily Zulaikhah (Universitas STRADA Indonesia, 2024)
Background: Adolescent who experience puberty in their bodies appear sex hormones that begin to work, resulting in a sense of attraction to the opposite sex. Premarital sex is a behavior that is carried out based on sexual desire in adolescents. Adolescent knowledge and sources of information received by adolescents are important points in efforts to prevent premarital sexual behavior. The preventive efforts can be done by providing education about the right information through various methods and media. One of them is education using flashcard media. Purpose: The purpose of this study was to analyze the effect of education on premarital sexual behavior using flashcard media. Methods: This study design was a quasi-experimental pre-test-post test design with control group. The number of samples were 60 which were divided into two groups and the inclusion criteria being adolescents aged 15-17 years and were or had been dating. The intervention group received treatment in the form of pre-marital sexual behavior education with flashcard media. The control group received pre-marital sexual behavior education using the lecture method. Before and after the intervention, researchers conducted a pretest and posttest using a pre-marital sexual behavior questionnaire and data were analyzed using the Wilcoxon test. Results: There was a difference in the average score of premarital sexual behavior in the intervention group after receiving flashcard education intervention with p value = 0.010 (p <0.05). Conclusion: Education using flashcard affects premarital sexual behavior in adolescents. Preventive and promotive efforts of premarital sexual behavior in adolescents using flashcard media are an alternative for nurses in providing counseling.